Risk assessment of chemical substances of safety concern generated in processed meats - Mónica Flores; Leticia Mora; Milagro Reig; Fidel Toldrá (Food Science and Human Wellness)
This manuscript is reviewing the presence of substances of safety concern that may be generated in different types of meat products. Such substances include N-nitrosamines that can be generated under certain conditions when using nitrite as preservative, the polycyclic aromatic hydrocarbons generated as a consequence of particular smoking processes, heterocyclic aromatic amines generated under particular cooking conditions, compounds released from the oxidation of lipids and proteins, Maillard reaction products like acrylamide and carboxymethyl lysine, and amines that can be generated and accumulated in fermented meats. These hazardous compounds, their mechanisms of generation, risks for health and ways of preventing its presence in meat products are briefly described in this review. Keywords: Polycyclic aromatic hydrocarbons, Heterocyclic amines, Nitrosamines, Amino acids oxidation, Lipids oxidation, Maillard reaction products, Biogenic amines